Photoinduced p‐ to n‐type Switching in Thermoelectric Polymer‐Carbon Nanotube Composites. Issue 14 (8th February 2016) - Dörling, Bernhard; Ryan, Jason D.; Craddock, John D.; Sorrentino, Andrea; Basaty, Ahmed El; Gomez, Andrés; Garriga, Miquel; Pereiro, Eva; Anthony, John E.; Weisenberger, Matthew C.; Goñi, Alejandro R.; Müller, Christian; et al.
Abstract : UV‐induced switching from p‐ to n‐type character is demonstrated during deposition of carbon‐nanotube–conjugated polymer composites. This opens the possibility to photopattern n‐type regions within an otherwise p‐type film, which has a potential for complementary circuitry or, as shown here, thermoelectric generators made from a single solution.